2021
DOI: 10.3390/ijms22115693
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dynamics Markers and Related Signaling Molecules Are Important Regulators of Spermatozoa Number and Functionality

Abstract: Here, we study possible mechanisms of (in/sub)fertility related to the acute or repeated psychological stresses (the most common stresses in human society) by following the transcriptional profile of 22 mitochondrial dynamics/function markers and 22 signaling molecules regulating both mitochondrial dynamics and spermatozoa number/functionality. An in vivo study mimicking acute (once for 3 h) and repeated (3 h for 10 consecutive days) psychophysical stress was performed on adult rats. The analysis of hormones, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 72 publications
1
23
0
Order By: Relevance
“…All experiments were performed in the Laboratory for Reproductive Endocrinology and Signaling and Laboratory for Chronobiology and Aging, Faculty of Sciences at University of Novi Sad (https://wwwold.dbe.pmf.uns.ac.rs/en/nauka-eng/lares, accessed on 4 March 2022). All the methods used in this study were previously reported by our group (for all references, please see [21,22,36]) and followed the relevant guidelines and regulations.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…All experiments were performed in the Laboratory for Reproductive Endocrinology and Signaling and Laboratory for Chronobiology and Aging, Faculty of Sciences at University of Novi Sad (https://wwwold.dbe.pmf.uns.ac.rs/en/nauka-eng/lares, accessed on 4 March 2022). All the methods used in this study were previously reported by our group (for all references, please see [21,22,36]) and followed the relevant guidelines and regulations.…”
Section: Methodsmentioning
confidence: 99%
“…Animals were bred and raised in the accredited Animal Facility of the Faculty of Sciences, University of Novi Sad, Serbia, in controlled environmental conditions (22 ± 2 • C; 14 h light and 10 h dark cycle, lights on at 7:00 a.m.) with food and water ad libitum. The experimental model of psychophysical stress by immobilization was performed using the method previously described [20][21][22]. In short, stressed (3hIMO) rats were bound in a supine position to a wooden board by fixing the rats' limbs using thread, while the head motion was not limited.…”
Section: Animals and Experimental Model Of Stressmentioning
confidence: 99%
See 3 more Smart Citations